Challenges in Ph.D studies: the case of arts student - Zainal Abiddin, Norhasni (Eurojournals, 2007)
Ph.D students have to take responsibility managing their own learning and getting a Ph.D. They are also responsible for determining what is required as well as for carrying it out, and must always keep in touch in regular meetings with the supervisor. The student is the main person responsible for his/her Ph.D research. Doing a Ph.D clearly indicates that this is a student's own research and work. The actual research using case study method where three Malaysian Ph.D students from three major disciplines of study namely arts, science and social science were involved. However only one case study which focusing on Arts discipline will be presented in this article. The reason being there were too many quotations have to be put in if better understanding of the story is to be achieved. This would make the article be too long if three case studies to be presented in this article. The objective of this research is to provide better guidelines for effective roles of a Ph.D Arts student especially the foreign student. As a result, the research had developed the best effective roles in order for students to success in their study.